Establishment of CRISPR/Cas9 Genome Editing in Witloof (Cichorium intybus var. foliosum) - De Bruyn, Charlotte; Ruttink, Tom; Eeckhaut, Tom; Jacobs, Thomas; De Keyser, Ellen; Goossens, Alain; Van Laere, Katrijn (Frontiers in Genome Editing, 2020)
Cichorium intybus var. foliosum (witloof) is an economically important crop with a high nutritional value thanks to many specialized metabolites, such as polyphenols and terpenoids. However, witloof plants are rich in sesquiterpene lactones (SL) which are important for plant defence but also impart a bitter taste, thus limiting industrial applications. Inactivating specific genes in the SL biosynthesis pathway could lead to changes in the SL metabolite content and result in altered bitterness. In this study, a CRISPR/Cas9 genome editing workflow was implemented for witloof, starting with polyethylene glycol (PEG) mediated protoplast transfection for CRISPR/Cas9 vector delivery, followed by whole plant regeneration and mutation analysis. Protoplast transfection efficiencies ranged from 20 % to 26 %. A CRISPR/Cas9 vector targeting the first exon of the phytoene desaturase (CiPDS) gene was transfected into witloof protoplasts and resulted in the knockout of CiPDS, giving rise to an albino phenotype in 23 % of the regenerated plants. Further implementing our protocol, the SL biosynthesis pathway genes germacrene A synthase (GAS), germacrene A oxidase (GAO) and costunolide synthase (COS) were targeted in independent experiments. Highly multiplex (HiPlex) amplicon sequencing of the genomic target loci revealed plant mutation frequencies of 27.3 %, 42.7 % and 98.3 % in regenerated plants transfected with a CRISPR/Cas9 vector targeting CiGAS, CiGAO and CiCOS, respectively. We observed different mutation spectra across the loci, ranging from consistently the same +1 nucleotide insertion in CiCOS across independent mutated lines, to a complex set of 20 mutation types in CiGAO across independent mutated lines. These results demonstrate a straightforward workflow for genome editing based on transfection and regeneration of witloof protoplasts and subsequent HiPlex amplicon sequencing. Our CRISPR/Cas9 workflow can enable gene functional research and faster incorporation of novel traits in elite witloof lines in the future, thus facilitating the development of novel industrial applications for witloof.